Corticosteroids in Patients with IgA Nephropathy and Severe Chronic Renal Damage - Claudio Pozzi; Francesca Ferrario; Bianca Visciano; Lucia Del Vecchio (Case Reports in Nephrology)
Little is known about the utility of treating patients with advanced IgA nephropathy (IgAN). From 2001 to 2005, four patients came to our observation because of serum creatinine higher than 3 mg/dL, proteinuria ranging from 1.8 to 5.1 g/day, and a histological picture of diffuse sclerotic lesions. A corticosteroid course of 12 months was given. Patients were observed for a mean follow up of 84 months. At the end of the steroid course, proteinuria lowered quickly below 1 g/day in two patients, whereas the other two experienced a slower and less persistent decrease of proteinuria. Despite similar lesion severity at renal biopsy, renal function stabilized only in these two ones. In conclusion, these preliminary observations suggest a possible efficacy of corticosteroids in slowing down the progression of renal disease and in postponing the need of dialysis in IgAN patients with stage IV CKD and severe chronic histological lesions.